2013
DOI: 10.1371/journal.pone.0076391
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mapping of Regional Expression of the Clock Protein PERIOD2 in Rat Forebrain across the 24-h Day

Abstract: In mammals, a light-entrainable clock located in the suprachiasmatic nucleus (SCN) regulates circadian rhythms by synchronizing oscillators throughout the brain and body. Notably, the nature of the relation between the SCN clock and subordinate oscillators in the rest of the brain is not well defined. We performed a high temporal resolution analysis of the expression of the circadian clock protein PERIOD2 (PER2) in the rat forebrain to characterize the distribution, amplitude and phase of PER2 rhythms across d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 84 publications
(92 reference statements)
8
51
1
Order By: Relevance
“…Interestingly, the present study indicates the similarity in this PER2 expression between a diurnal primate and diurnal rodents (Amir et al, 2006), and consequently, the differences with nocturnal rodents (Mrosovsky et al, 2001;Vosko et al, 2009). Although this antiphase in the PER2 expression between SCN and hippocampus also exists in nocturnal rodents, in these animals the PER2 in the SCN peaks at ZT 12 in the night phase and in the hippocampus the PER2 peak happens in ZT 0 (light phase) in both LD and DD conditions (Harbour et al, 2013;Pantazopoulos et al, 2011;Wang et al, 2009). Many features of the SCN are the same in diurnal and nocturnal animals, suggesting that differences in phase preference are determined by mechanisms downstream from the SCN.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, the present study indicates the similarity in this PER2 expression between a diurnal primate and diurnal rodents (Amir et al, 2006), and consequently, the differences with nocturnal rodents (Mrosovsky et al, 2001;Vosko et al, 2009). Although this antiphase in the PER2 expression between SCN and hippocampus also exists in nocturnal rodents, in these animals the PER2 in the SCN peaks at ZT 12 in the night phase and in the hippocampus the PER2 peak happens in ZT 0 (light phase) in both LD and DD conditions (Harbour et al, 2013;Pantazopoulos et al, 2011;Wang et al, 2009). Many features of the SCN are the same in diurnal and nocturnal animals, suggesting that differences in phase preference are determined by mechanisms downstream from the SCN.…”
Section: Discussionsupporting
confidence: 59%
“…Somewhat contrastingly, studies by (28) showed that peak expression of Per2 in the hippocampus was found between ZT23 and ZT2 while lowest expression was at ZT10. (12) showed that Per2 expression in the dentate gyrus, CA1 and CA3 sub-regions of the hippocampus peak at ZT22, ZT21.5 and ZT23.5 respectively in rats. It is difficult to make direct comparisons as the rodent species, age, method of expression measurement, time-point and brain tissue sampling technique differs from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For e.g. Harbour et al, (12) analysing Per2 expression in 20 forebrain areas showed that peak expression of Per2 immunoreactive cells in the SCN occurred in the early part of the dark phase, at ZT 14.25. Using transgenic rats expressing the firefly luciferase gene under the control of the mouse Per1 promoter, (25) investigated the intrinsic rhythmicity of Per1 in isolated brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this experiment, the higher expression time point (13:00) during the light phase and lower expression time point of Per2 (1:00) during the dark phase based on zhao's study were selected to test the effects of SCN lesion on Per2 and c-fos mRNA expression The result in normal rats showed that there was high Per2 and c-fos mRNA level on 13:00 and low level on 1:00, which was coincident with the Zhao's (Zhao, 2015) and had similar trend with firing rates of neurons in Hb (Zhao, 2005). The characteristics of this rhythm are also consistent with that of the SCN neurons under LD condition (Harbour, 2013;Inouye, 1982;Rocha, 2014). Further, in the SCN lesioned experiment we found the difference of Per2 and c-fos mRNA expression in the Hb at the 13:00 and 1:00 disappeared after the SCN lesion, suggesting that the rhythmic expression in the Hb may denpend on the presence of the SCN.…”
Section: Discussionmentioning
confidence: 72%